A Broadcast Disk scheme for mobile information system - Sumari, Putra (2010)
The rapidly expanding technology of cellular communications, wireless local area network (LAN), wireless data networks and satellite gives mobile users the ability of accessing information anywhere and anytime. Data broadcasting algorithm plays an important role as it instructs the server to disseminate large amount of data at a fast rate to many mobile clients. One of the work known as the Broadcast Disk method creates a sequence of slots containing data and broadcasts them in a circular manner on the air. Mobile clients keep listening to the air and catch those slots that interest them. However in the Broadcast Disk method, some slots are empty, which results to waste of resources and increase in clients' average waiting time. Empty slots are randomly generated and difficult to be located. In this paper we present a scheme called the Optimum Broadcast Disk, which is an enhancement of the Broadcast Disk method to overcome the empty slots issue and hence reduce the users' waiting time. We manage to locate these empty slots and fill them with popular data. We demonstrate by case studies and simulation that our scheme eliminates empty slots and minimizes clients' average waiting time.